Two-way FDI and corporate total factor productivity--moderating role of environmental information disclosure quality - Yu Duan; Yutong Ruan (PLoS ONE, 2026)
This paper takes A-share Chinese listed companies from 2011 to 2021 as research samples and discusses the effects and potential moderating mechanisms of two-way FDI on corporate total factor productivity. Firstly, It is empirically found that the impact of corporate inward foreign direct investment (IFDI) on its own total factor productivity (TFP) is higher than that brought by outward foreign direct investment (OFDI). After a series of robustness tests, the baseline results are still firm and valid. Secondly, moderating analyses demonstrate that both corporate environmental information disclosure quality and technological innovations exert significant moderating effects on the relationship between two-way FDI and corporate total factor productivity. Thirdly, this paper finds that the effects of two-way FDI faced by listed companies in the central and western regions, non-heavily polluting companies and state-owned listed companies are more significant. Finally, this paper clarifies that policies should be formulated according to local conditions to promote fair competition among enterprises efficiently while reducing the investment and financing thresholds for small enterprises, so as to improve the international competitiveness of Chinese enterprises in various fields as soon as possible.